국민주택기금운용의 개선방안에 대한 연구 -주택도시기금의 도입을 중심으로 - 남영우(Nam, Young Woo); 김행조(Kim, Haeng Jo) (대한부동산학회지, 2014)
국민주택기금은 지난 30년이 넘도록 우리나라의 주택공급 및 주거안정에 크게 기여해 왔다. 하지만 최근 주택시장의 환경이 변화하면서 기금의 운용방향에도 변화가 필요하게 되었다. 최근 주택시장의 주요 변화방향을 살펴보면 주택시장의 장기안정화와 도시의 노후화로 인한 도시재생사업의 필요성 증대, 공공임대주택을 공급으로 인한 LH공사의 부실화 등이 있다. 이러한 각각의 요인들은 기금의 운용에 있어서도 크게 영향을 미치게 된다. 따라서 새로운 시장환경에 부합하는 기금운용의 변화가 필요할 것으로 보인다. 정부에서는 최근 변화하는 시장환경에 대비하기 위해서 기존의 국민주택기금을 주택도시기금으로 개변하는 개선방향을 제시하였다. 이번 개편방향을 살펴보면 기금의 지원대상을 주택뿐만 아니라 도시도 포함하여 도시재생을 지원할 수 있는 근거를 마련하고 지원방식도 현재까지의 단순융자방식에서 직접투자와 메자닌방식의 투자 및 채무보증까지 확대하는 방안을 포함하였다. 이를 위해서 기존에 금융기관에 위탁하였던 운용체계를 전담운용기관을 두는 방향으로 개선하는 내용을 제시하였다. 본 연구에서는 새로운 기금운용의 개선방향을 살펴보고 도시재생사업 지원과정에서 투명성확보와 투자방식의 사업에서 발생할 수 있는 리스크관리 등이 기금의 개편과정에서 선결되어야 할 과제로 제시하였다. The National Housing Fund has greatly contributed to housing supply and residential stabilization in Korea for the last 30 years. But with the recent change of the housing market, there has been a need to change the direction for its operation. Investigation of the recent major change of the housing market shows that it has many problems such as the increase of the need for the urban regeneration project due to the long-term stabilization of the housing market and the deterioration of the city, the deterioration of LH Corporation due to the supply of public rental housing and the like. Each of these factors has come to have a great effect on the operation of the fund. Accordingly, it is thought that it is necessary to change it to fit a new market environment. Government has presented a direction for its improvement of changing from the existing National Housing Fund to the urban housing fund in preparation for a newly changing market environment. Investigation of the direction for its reorganization shows that it includes the scheme for providing the foundation for supporting urban regeneration by incorporating cities as well as housing into those subject to support to cities as well as housing and for extending the method of support from the simple financing method to direct investment and Mezzanine-type investment and obligation guarantee. For this purpose, it has presented the method of improving the fund in a direction of putting the operating system entrusted to the financial institution into the exclusive operation institution. This study attempted to investigate a new direction for improvement of fund operation and presented the tasks to be settled in a process of reorganizing the fund, such as the securing of transparency in a process of supporting the urban renewal project, the management of risks likely to arise from the investment-type project and the like. KCI Citation Count: 11